Penerapan Metode Iqra’ dalam Pembelajaran Membaca al-Qur’an di MDTA Ar-Rahman Jorong Koto Laweh Kecamatan Tilatang Kamang Kabupaten Agam - Yosi Yosi; Arman Husni (Lembaga Yasin AlSys, 2026)
Qur’an reading instruction through the Iqra’ method has received attention in various studies because it is considered effective in helping students recognize hijaiyah letters and gradually improve their reading ability. Nevertheless, studies that specifically discuss the implementation of the Iqra’ method along with supporting factors, inhibiting factors, and teacher strategies in optimizing its application in the context of madrasah diniyah remain relatively limited. This study aims to describe the application of the Iqra’ method in Qur’an reading instruction at MDTA Ar-Rahman Jorong Koto Laweh, Tilatang Kamang Subdistrict, Agam Regency, and to analyze the factors that influence its success. This study uses a qualitative approach with a case study design. The research informants included the head of the madrasah, teachers, and students selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using thematic analysis through the stages of data reduction, data presentation, and conclusion drawing. The results show that the Iqra’ method was applied gradually and individually with the support of learning media and intensive guidance from teachers, thereby improving students’ Qur’an reading ability. The success of implementation was influenced by teacher competence, the use of media, and parental involvement, whereas differences in students’ initial abilities and limited facilities were the main obstacles. The conclusion of this study affirms that the effectiveness of the Iqra’ method in Qur’an reading instruction depends on the integration of pedagogical strategies, learning media, teacher guidance, and family collaboration. The implications of this study provide a foundation for developing more adaptive Qur’an learning practices and serve as a reference for further research on innovations in technology-based and collaborative approaches to Qur’an learning methods.